An observational study on benign/malignant gastric outlet obstruction in tertiary care centre of RIMS, Ranchi, India - Kumar, Amit; Alam, Md. Afsar; Kumar, Jitendra; Tiwary, A. K. (International Surgery Journal, 2017)
Background: Gastric outlet obstruction is a group of clinico-patho physiological consequence of mechanical impediment of gastric emptying. Clinical entities that can result in gastric outlet obstruction are categorized into two well-defined groups of causes - benign and malignant. The proximal stomach is now the most common site for gastric carcinoma in the west but in Japan and developing countries like India the distal gastric cancer (antrum 13% and pylorus 7%) still predominates. Diagnosis of gastric outlet obstruction depends on different clinical features and certain investigations. The definitive treatment involves surgical relief of the gastric outlet obstruction. The correct surgical procedure to be adopted is planned according to the cause of obstruction and condition of the patients. This is an observational study aimed for characterization of gastric outlet obstruction in terms of benign and malignant and their relation to its causes, sites and other related factors in tertiary care centre (RIMS). Methods: This is an observational study comprises on 50 patients of gastric outlet obstruction admitted in the Department of Surgery R.I.M.S., Ranchi. The provisional diagnosis was based on detailed clinical history, thorough physical examinations, and some radiological investigations. Results: Majority of the patients of gastric outlet obstruction were malignant lesions of stomach and very few are benign. Antral carcinoma of stomach was found to be the commonest etiology of gastric outlet obstruction followed by pyloric stenosis secondary to acid peptic disorders. Most of the patient was in the age group of 40 to 60 years of age, males were affected more than Females. Conclusions: Gastric outlet obstruction in adults, a surgical problem of either sex, results commonly due to antral carcinoma or pyloric stenosis secondary to acid peptic disorder.